DIGITAL TRANSFORMATION OF THE GLOBAL EDUCATIONAL ENVIRONMENT - RYBCHUK, ANATOLIY; ZHURBA, IHOR; PROTSYSHYN, OKSANA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The phenomenon of digitalization of education is interconnected with the features of the modern generation, which is rapidly integrating into the global educational space. Active involvement of personalized services in the lives of young people exacerbates the problem of finding new educational technologies, updating the content of education to meet individual educational needs, personal and professional self-determination in the context of their life and career growth. Digitalization of the educational environment expands the possibilities of communication, changes the social situation, transforms the motivational and value sphere, affects the personal and professional self-determination of students as a digital generation immersed in the digital environment and digital communications, the bearer of computer-generated values , mobile devices, Internet, social networks. The digitalization of education is a powerful trend in reforming and modernizing the global educational environment and involves the conversion of all types of information from various sources into digital language. Forecasts suggest the transition of the learning process to a digital environment as a turning point in the history of education.The article investigates the preconditions and current trends in the global digitalization of education. The necessity of using new digital pedagogical technologies is reasoned and the possibilities of access to various tools for expanding the field of blended learning are outlined. It is confirmed that the digitalization of the educational environment expands the boundaries of communication, changes the social situation, transforms the motivational and value sphere, affects the personal and professional self-determination of students. It was found that the introduction of the digital technologies in education is the dominant trend of reforming and modernizing the global educational environment and involves the conversion of all types of information into digital language.
Keywords: digitalization of education; global educational environment; digital communications; digital pedagogical technologies; digital language; pedagogical technologies of distance learning